2013
DOI: 10.1002/adsc.201200808
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Asymmetric Organocatalytic Construction of 3,3′‐Spirocyclic Oxindoles

Abstract: The asymmetric organocatalysis is definitely one of the most powerful and versatile tools for the rapid construction of various spirocyclic oxindoles. In the past few years, a number of successful strategies based on organocatalysis have been developed for the construction of 3,3′‐spirocyclic oxindoles in high yields and excellent enantioselectivities under mild conditions. In this review, recent advances in this area are summarized and classified according to the spiro ring fused at the 3‐position of the oxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
112
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 693 publications
(113 citation statements)
references
References 112 publications
0
112
0
1
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36][37][38][39][40] Recently, we successfully found that spiro[indoline-3,1'-quinolizin]-2-ones, which were generated from the three-component reaction of substituted pyridine, acetylenedicarboxylate and 3-phenacylideneoxindoles, could undergo Diels-Alder reaction with the typical dienophiles such as maleic anhydride and N-phenylmaleimides. [41][42][43] Alternatively, spiro[3H-indole-3,2'-[2H,9aH-pyrido [2,1-b] [1,3]oxazine], which were formed from three-component reaction of the substituted pyridines, electron-deficient alkynes and isatins, also underwent Diels-Alder reaction with 3-phenacylideneoxindoles (eq. 1 in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30][31][32][33][34][35][36][37][38][39][40] Recently, we successfully found that spiro[indoline-3,1'-quinolizin]-2-ones, which were generated from the three-component reaction of substituted pyridine, acetylenedicarboxylate and 3-phenacylideneoxindoles, could undergo Diels-Alder reaction with the typical dienophiles such as maleic anhydride and N-phenylmaleimides. [41][42][43] Alternatively, spiro[3H-indole-3,2'-[2H,9aH-pyrido [2,1-b] [1,3]oxazine], which were formed from three-component reaction of the substituted pyridines, electron-deficient alkynes and isatins, also underwent Diels-Alder reaction with 3-phenacylideneoxindoles (eq. 1 in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Thus, spirooxindole has attracted much interests in synthetic and medical chemistry. [4][5][6][7][8][9] In many elegant synthetic methods for various spirooxindole systems, the multicomponent reactions or domino reactions have emerged as one of the efficient strategies, [10][11][12] which can provide diverse spirooxindoles in an operationally simple one-pot procedure from readily available chemical reagents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the sharing of the 3-carbon indole atom during the production of spiroindoline derivatives can greatly increase biological activity (6). Many efficient and applied methods have been reported for the synthesis of versatile spirooxindole-fused heterocycles (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Such developments are of interest not only for the possible total synthesis of therapeutically useful spirooxindoles [6][7][8][9][10][11][12][13][14][15], but also for the preparation of synthetic analogs [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] in order to improve our knowledge in structure-activity relationships [12-14, 31, 32]. So-called butenolide functionalized spirooxindoles 1 provide the most interesting subject for synthetic investigations in view of the large and ever increasing number of the members of this family which have furan-2(5H)-one 2 as a building block (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%